Pendampingan Kegiatan Literasi di SMP Negeri 2 Kalabahi dalam Masa Penugasan Program Kampus Mengajar Angkatan IV - Lois Letidena; Oktovian Meriance Lonawata; Ronapli Blegur Wabang; Jeni Marianti Loban; Melki Imamastri Puling Tang (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Literacy activities are activities that are being actively encouraged to become a culture in the world of education. It is hoped that literacy activities will become a new culture and habit. The Independent Campus Learning Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. The Teaching Campus Program is one of the programs in the Independent Campus Learning Program (MBKM) which has the aim of assisting literacy, numeracy, technology adaptation learning, assisting school administration and teachers. One of the schools targeted in the Teaching Campus Program Batch 4. UPTD SMP NEGERI 2 KALABAHI is one of the target schools for teaching campus activities (KM4), this school is located in East Welai Village, Teluk Mutiara District, Alor Regency, East Nusa Tenggara. Literacy activities that we carry out include making a literacy schedule every day, making class bulletins for literacy activities in class and outside the classroom, making fruit name charts in Latin, Indonesian and English. Students are actively involved in every activity. Literacy, numeracy, technology adaptation, assisting school administration, and helping improve and improve student character and student interest in learning with various kinds of creative learning.